Win in Chinese courts : practice guide to civil litigation in China - Zhang, Chenyang (Springer, 2023)
This open access book aims to provide an initial but comprehensive roadmap for the Chinese civil litigation system. It starts with some basic concepts of the Chinese judicial system (e.g., court system, case numbering, hierarchical trial system, etc.) and runs through the entire process and most aspects of civil litigation cases (e.g., jurisdiction, service of process, rules of evidence, enforcement, representative actions, etc.). The first target audience for this book is lawyers outside of mainland China. For professors and law students, this book also serves as a window into the Chinese judicial system in a short period of time. It is my hope that this book serves as a backdrop for additional observations of Chinese judicial practice, such as a review of recent cases. This is an open access book.